Subjective social status and trajectories of frailty: findings from the English Longitudinal Study of Ageing - Patrick Präg; Lindsay Richards; Asri Maharani (BMJ Public Health)
Objectives Subjective social status is a known antecedent for many health outcomes, but little research has examined the association between subjective status and frailty among older people. Using longitudinal data, the goal of this study was, first, to identify latent trajectories of frailty over time, and second, to investigate the relationship between subjective social status and frailty trajectory.Methods Data were drawn from the 2002–2019 surveys of the English Longitudinal Study of Ageing, involving 9484 individuals aged 50+ years at baseline. Group-based trajectory models were used to identify frailty trajectories over the 18-year period, and multinomial regression models were used to investigate the relationship between subjective social status and frailty trajectory membership. Controls were included for confounding factors, including a range of socioeconomic indicators and health behaviours.Results Four trajectories of the frailty index were retained: low frailty (53% of participants), progressive mild frailty (25%), progressive moderate frailty (15%) and high frailty (6%). Higher subjective social status is associated with higher probabilities of being in the low-frailty group and lower probabilities of being in one of the progressive or high-frailty groups.Conclusions Subjective social status is significantly associated with being in a milder frailty trajectory after controlling for age, health behaviours and a wide range of objective socioeconomic status markers.